Предмет: Алгебра,
автор: ПоЛиНкАаА228
Помогите пожалуйста,преобразование рациональных выражений,8 класс
Приложения:
Ответы
Автор ответа:
0
1/(b-3)-6b/(b²-9)·(1/(b-2)-2/(b²-2b))=1/(b-3)-6b/(b²-9)·((b-2)/b(b-2))=
=1/(b-3)-6b/(b²-9)·1/b=1/(b-3)-6b/b(b²-9)=(b(b+3)-6b)/b(b²-9)=(b²+3b-6b)/b(b-3)(b+3)=
=b(b-3)/b(b-3)(b+3)=1/(b+3)
=1/(b-3)-6b/(b²-9)·1/b=1/(b-3)-6b/b(b²-9)=(b(b+3)-6b)/b(b²-9)=(b²+3b-6b)/b(b-3)(b+3)=
=b(b-3)/b(b-3)(b+3)=1/(b+3)
Похожие вопросы
Предмет: Русский язык,
автор: emilbalasultanov1
Предмет: Английский язык,
автор: Аноним
Предмет: Биология,
автор: kristithehugger
Предмет: Физика,
автор: ayurkabaldanov